2016
DOI: 10.1177/1479972316642365
|View full text |Cite
|
Sign up to set email alerts
|

Use of predictive algorithms in-home monitoring of chronic obstructive pulmonary disease and asthma

Abstract: Major reported factors associated with the limited effectiveness of home telemonitoring interventions in chronic respiratory conditions include the lack of useful early predictors, poor patient compliance and the poor performance of conventional algorithms for detecting deteriorations. This article provides a systematic review of existing algorithms and the factors associated with their performance in detecting exacerbations and supporting clinical decisions in patients with chronic obstructive pulmonary disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
79
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(80 citation statements)
references
References 93 publications
(134 reference statements)
1
79
0
Order By: Relevance
“…While most previous COPD telemonitoring studies collected data daily, [11] the one study with more frequent collection used a custom wristband that was designed to perform 5 measurements of their oxygen saturation, heart rate, body temperature, and physical activity every 3 hours. [18] However, they obtained on average only 4 recordings per patient day, and data was available for only 60% of patient days, seemingly due to lack of use of their system.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…While most previous COPD telemonitoring studies collected data daily, [11] the one study with more frequent collection used a custom wristband that was designed to perform 5 measurements of their oxygen saturation, heart rate, body temperature, and physical activity every 3 hours. [18] However, they obtained on average only 4 recordings per patient day, and data was available for only 60% of patient days, seemingly due to lack of use of their system.…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review examined the effectiveness of home telemonitoring of people with COPD in predicting AECOPD. [11] Of the 16 studies that evaluated the predictive ability of systems that recorded physiologic parameters and/or symptoms, none appeared to be clinically reliable in predicting AECOPDs. One reason may be that most data is collected too infrequently.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is increasing interest in the development of more accurate predictive algorithms using machine learning; Sanchez-Morillo [ 38 ] and colleagues in a recent review concluded that while some of these show promise that they have been based on relatively small numbers of patients and events. [ , who used logistic regression to predict future exacerbations and showed that using pulse rate, oxygen saturation, and respiratory rate (from a pulse oximeter) showed improved predictivity when compared with traditional algorithms of COPD exacerbations.…”
Section: Comparison With Prior Workmentioning
confidence: 99%